Sisterhood is global : the international women's movement anthology - Morgan, Robin (Open Road Media, 2016)
A powerful and essential anthology that sheds light on the status of women throughout the world Hailed by Alice Walker as "one of the most important human documents of the century," this collection of groundbreaking essays examines the global status of women's experiences, from oppression to persecution. Originally published in 1984, the compilation features pieces written by a diverse set of powerful women-journalists, politicians, grassroots activists, and scholars-from seventy countries. Author Robin Morgan, a champion of women's rights herself, expertly weaves these inspiring essays into one comprehensive feminist text. These compelling "herstories" contain thoroughly researched statistics on the status of women throughout the world. Each chapter focuses on a different country and includes data on education, government, marriage, motherhood, prostitution, rape, sexual harassment, and sexual preference. Sisterhood Is Global transcends political systems and geographical boundaries to unite women and their experiences in a way that remains unequalled, even decades after its first publication